Elaboración de un Guía de avifaunística en el Recinto Macuchí, parroquia El Tingo La Esperanza, cantón Pujilí, provincia de Cotopaxi. - Marcalla Molina, Erika Vanessa (2018)
This research will aim to design a bird guide, by applying techniques and tools that allow the carrying out of an avifaunistic inventory in the Macuchí Campus, El Tingo la Esperanza Parish, Pujilí Canton, Cotopaxi Province. For which three specific objectives are proposed: to carry out a situational diagnosis, inventory and the preparation of the bird guide. The situational diagnosis will determine the geographical position, physical characteristics and the type of vegetation, which are factors that will allow establishing the type of habitat and species; since the factors determine the avifaunística wealth of the sector. Bibliographic research and review of websites that contain information corresponding to the indicated geographic space will contribute to the collection of information to determine the current state of the area. The direct count will be a fundamental part of the investigation since it will allow the registration and identification of the bird species in the area. After the information collected from the diagnosis and the inventory will be used to prepare the guide. In addition, the guide will contain the taxonomic classification (order, family, genus and species); The files will be arranged according to the order and family of each species, as well as the content of information regarding the common name, family, scientific name, name in English and description, the respective photograph where each species will be clearly shown, allowing the recognition of birds in the field. As a result of the work, the design of a birdlife guide for the sector will be concluded, using technological means that allow its development.